Optical laminate film and manufacturing method

The optical laminated film addresses variations in light resistance by using a thermoplastic resin with an alicyclic structure, an ultraviolet absorber, and a hindered amine light stabilizer, ensuring uniform mixing and distribution of additives, thereby achieving consistent and enhanced light resistance.

JP7666270B2Active Publication Date: 2025-04-22ZEON CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021158040
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-28
Publication Date
2025-04-22
Estimated Expiration
2041-09-28

AI Technical Summary

Technical Problem

Resin films containing ultraviolet absorbers and light stabilizers often exhibit variations in light resistance across the plane, due to uneven distribution of additives during the manufacturing process.

Method used

An optical laminated film is developed with a specific composition and structure, including a thermoplastic resin with an alicyclic structure, an ultraviolet absorber, and a hindered amine light stabilizer. The melting points of the ultraviolet absorber and the light stabilizer are controlled to ensure they mix well, and their average melting point is set above the glass transition temperature of the thermoplastic resin, thereby suppressing variations in light resistance.

Benefits of technology

The optical laminated film achieves uniform light resistance across the plane, reducing variations and enhancing the film's overall light resistance properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666270000006
    Figure 0007666270000006
  • Figure 0007666270000007
    Figure 0007666270000007
  • Figure 0007666270000001
    Figure 0007666270000001
Patent Text Reader

Abstract

To provide an optical laminated film in which variations in light resistance are suppressed, and a method of manufacturing the same.SOLUTION: There is provided an optical laminated film comprising: a first outer layer; an intermediate layer; and a second outer layer in this order. The intermediate layer is an A layer that includes: a resin containing an alicyclic structure-containing polymer [1] having a glass transition temperature Tg1 (°C); an ultraviolet absorber [1] having a melting point Mp1 (°C); and a hindered amine-based light stabilizer [1] having a melting point Mp2 (°C). A proportion of the alicyclic structure-containing polymer [1], a proportion of the ultraviolet absorber [1], and a proportion of the hindered amine-based light stabilizer [1] based on the entire layer A are each within a predetermined range. The Tg1, the Mp1 and the Mp2 satisfy the following formulas (1) and (2). Formula (1): |(Mp1-Mp2)|≤100(°C). Formula (2): (Mp1+Mp2) / 2}-Tg1>0(°C).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical laminate film and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art Conventionally, in order to impart light resistance (ultraviolet light resistance) to a resin film, a technique of adding an ultraviolet absorbing agent or a light stabilizer to the resin film has been used (Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-33517 A [Patent Document 2] JP 2017-116759 A [Patent Document 3] JP 2017-23038 A Summary of the Invention [Problem to be solved by the invention]

[0004] Resin films containing additives such as ultraviolet absorbers and light stabilizers may have in-plane variations in light resistance.

[0005] The present invention has been devised in view of the above problems, and an object of the present invention is to provide an optical laminate film in which the variation in light resistance is suppressed, and a method for producing the same. [Means for solving the problem]

[0006] The present inventor has conducted research to achieve the above object. As a result, it has been found that in a resin film containing a thermoplastic resin containing an alicyclic structure-containing polymer, an ultraviolet absorber, and a hindered amine-based light stabilizer, the absolute value of the melting point difference between the melting point Mp1 of the ultraviolet absorber and the melting point Mp2 of the hindered amine-based light absorber is set to a predetermined value or less, and the average value of the melting points Mp1 and Mp2 is greater than the glass transition temperature Tg1 of the thermoplastic resin, by selecting each component, the in-plane light resistance variation of the resin film can be suppressed, and the present invention has been completed. The present invention includes the following.

[0007] [1] An optical laminate film comprising a first outer layer, an intermediate layer, and a second outer layer in this order, wherein the intermediate layer is an A layer containing a thermoplastic resin [1] having a glass transition temperature Tg1 (°C) and containing an alicyclic structure-containing polymer, an ultraviolet absorber [1] having a melting point Mp1 (°C), and a hindered amine-based light stabilizer [1] having a melting point Mp2 (°C), wherein the proportion of the thermoplastic resin [1] in the entire A layer is 70% by weight or more and 99.8% by weight or less, the proportion of the ultraviolet absorber [1] is 0.1% by weight or more and 20% by weight or less, and the proportion of the hindered amine-based light stabilizer [1] is 0.1% by weight or more and 10% by weight or less, and the Tg1, the Mp1, and the Mp2 satisfy the following formulas (1) and (2). |(Mp1-Mp2)|≦100(℃) (1) {(Mp1+Mp2) / 2}-Tg1>0(℃) (2) [2] The first outer layer and the second outer layer are each independently a B layer containing the thermoplastic resin [1] and particles, the proportion of the thermoplastic resin [1] in the entire B layer is 90% by weight or more and 98.8% by weight or less, the proportion of the particles is 1% by weight or more and 10% by weight or less, and the glass transition temperature Tg1 (°C) of the thermoplastic resin [1] is 120°C or more. The optical laminate film according to [1]. [3] The optical laminate film according to [2], wherein the layer B contains an ultraviolet absorber [2] and a hindered amine light stabilizer [2], the proportion of the ultraviolet absorber [2] in the entire layer B is 0.1% by weight or more and 5% by weight or less, the proportion of the hindered amine light stabilizer [2] is 0.1% by weight or more and 5% by weight or less, and the ultraviolet absorber [2] and the hindered amine light stabilizer [2] each independently have a 5% thermal weight loss temperature of 250°C or more. [4] The optical laminate film according to [2] or [3], wherein the total thickness of the optical laminate film is 10 μm or more and 100 μm or less, and the thickness of the B layer is 0.5 μm or more and 10 μm or less. [5] The optical laminate film according to any one of [1] to [4], wherein the haze (HZ) of the optical laminate film is 2% or less. [6] A method for producing the optical laminate film according to any one of [1] to [5], comprising producing the first outer layer, the intermediate layer and the second outer layer by melt co-extrusion. Effect of the Invention

[0008] According to the present invention, there are provided an optical laminate film with reduced variation in light resistance and a method for producing the same. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a cross-sectional view that typically shows a cross section of an optical layered film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a side view that illustrates a schematic diagram of an apparatus for producing an optical laminate film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0011] [1. Overview of optical laminated films] Fig. 1 is a cross-sectional view showing a schematic cross section of an optical laminate film according to one embodiment of the present invention. The optical laminate film 10 shown in Fig. 1 includes a first outer layer 111, an intermediate layer 120, and a second outer layer 112 in this order. In the optical laminate film 10, the intermediate layer 120 is an A layer (A) having a glass transition temperature Tg1 (°C) and including a thermoplastic resin [1] containing an alicyclic structure-containing polymer, an ultraviolet absorber [1] having a melting point Mp1 (°C), and a hindered amine-based light stabilizer [1] having a melting point Mp2 (°C).

[0012] In the optical laminate film 10 of this embodiment, the proportion of the thermoplastic resin [1] in the entire A layer is 70% by weight or more and 99.8% by weight or less, the proportion of the ultraviolet absorber [1] is 0.1% by weight or more and 20% by weight or less, and the proportion of the hindered amine light stabilizer [1] is 0.1% by weight or more and 10% by weight or less.

[0013] In the optical laminate film 10 according to this embodiment, Tg1, Mp1 and Mp2 satisfy the following formulae (1) and (2).

[0014] |(Mp1-Mp2)|≦100(℃) (1) {(Mp1+Mp2) / 2}-Tg1>0(℃) (2)

[0015] According to the present embodiment, since the intermediate layer is Layer A containing a thermoplastic resin [1], an ultraviolet absorber [1], and a hindered amine light stabilizer [1] that satisfy the formulas (1) and (2), it is possible to provide an optical laminate film in which the in-plane variation in light resistance is suppressed.

[0016] The present inventors speculate as follows about the mechanism by which the A layer satisfies the formulas (1) and (2) and thus the in-plane variation in light resistance of the optical laminate film can be suppressed. However, the technical scope of the present invention is not limited by the mechanism described below.

[0017] The in-plane variation in light resistance of a resin film containing additives such as an ultraviolet absorber and a light stabilizer is caused by unevenness in the concentration of the additives in the resin film. The unevenness in concentration is also caused by insufficient mixing of the components when the thermoplastic resin, the ultraviolet absorber, and the light stabilizer are melt-kneaded to form a resin composition during the production of the resin film.

[0018] One of the factors that cause uneven concentration of additives in a resin film is that additives such as ultraviolet absorbers and light stabilizers do not mix sufficiently with each other, which causes uneven distribution of the ultraviolet absorbers or uneven distribution of the light stabilizers. In this embodiment, the absolute value of the melting point difference between the melting point Mp1 of the ultraviolet absorber and the melting point Mp2 of the hindered amine light absorber is set to a predetermined value or less, that is, by selecting an ultraviolet absorber [1] and a hindered amine light absorber [1] that have close melting points so as to satisfy formula (1), the ultraviolet absorber [1] and the hindered amine light stabilizer [1] can be mixed well, so that uneven concentration due to uneven distribution of the ultraviolet absorber and uneven distribution of the hindered amine light stabilizer can be suppressed, and uniform light resistance can be achieved within the film plane.

[0019] Another factor that causes uneven concentration of additives in a resin film is that when a thermoplastic resin and additives such as an ultraviolet absorber and a light stabilizer are melted and kneaded to form a resin composition, the additives melt before the thermoplastic resin is sufficiently softened, and the thermoplastic resin and the additives cannot be sufficiently mixed, resulting in uneven distribution of the additives in the thermoplastic resin. In this embodiment, by increasing the difference between the average value of the melting point Mp1 of the ultraviolet absorber [1] and the melting point Mp2 of the hindered amine light stabilizer [1], which are additives, and the glass transition temperature Tg1 of the thermoplastic resin, that is, by selecting the thermoplastic resin [1], the ultraviolet absorber [1], and the hindered amine light stabilizer [1] so as to satisfy formula (2), the thermoplastic resin [1] can be well mixed with the additives in a sufficiently softened state during melt kneading, so that uneven concentration due to uneven distribution of the additives in the thermoplastic resin can be suppressed, and uniform light resistance can be achieved within the plane of the film.

[0020] [2. Middle layer (A layer)] The intermediate layer according to this embodiment is an A layer that includes a thermoplastic resin [1] having a glass transition temperature Tg1 (°C) and including an alicyclic structure-containing polymer, an ultraviolet absorber [1] having a melting point Mp1 (°C), and a hindered amine-based light stabilizer [1] having a melting point Mp2 (°C). The A layer includes the thermoplastic resin [1], the ultraviolet absorber [1], and the hindered amine-based light stabilizer [1] in a specific ratio. In addition, in the A layer, the glass transition temperature Tg1 (°C) of the thermoplastic resin [1], the melting point Mp1 (°C) of the ultraviolet absorber [1], and the melting point Mp2 (°C) of the hindered amine-based light stabilizer [1] satisfy a specific relationship.

[0021] [2.1. Relationship between Tg1, Mp1 and Mp2] In the layer A, the glass transition temperature Tg1 (℃) of the thermoplastic resin [1], the melting point Mp1 (℃) of the ultraviolet absorber [1], and the melting point Mp2 (℃) of the hindered amine light stabilizer [1] satisfy the following formulas (1) and (2).

[0022] |(Mp1-Mp2)|≦100(℃) (1) {(Mp1+Mp2) / 2}-Tg1>0(℃) (2)

[0023] Formula (1) is a relational expression showing the relationship between the melting point Mp1 of the ultraviolet absorber [1] and the melting point Mp2 of the hindered amine light stabilizer [1]. In this embodiment, the absolute value of the difference between the melting points Mp1 and Mp2 (|(Mp1-Mp2)|) is 100°C or less, so that the variation in light resistance within the film plane can be suppressed. (|(Mp1-Mp2)|) is usually 100°C or less, preferably 70°C or less. On the other hand, the lower limit of (|(Mp1-Mp2)|) can usually be 0°C or more, preferably 35°C or more, more preferably 50°C or more. In formula (1), Mp1 may be larger than Mp2, may be the same as Mp2, or may be smaller than Mp2, but it is preferable that Mp1 is larger than Mp2.

[0024] Formula (2) is a relational expression showing the relationship between the melting point Mp1 of the ultraviolet absorber [1] and the melting point Mp2 of the hindered amine light stabilizer [1] and the glass transition temperature Tg1 (°C) of the thermoplastic resin [1]. Formula (2) can also be regarded as a relational expression showing the relationship between the melting point of the additive and the glass transition temperature of the thermoplastic resin. In this embodiment, the difference ({(Mp1+Mp2) / 2}-Tg1) between the average value of the melting point Mp1 of the ultraviolet absorber [1] and the melting point Mp2 of the hindered amine light stabilizer [1] and the glass transition temperature Tg1 of the thermoplastic resin [1] is larger than 0°C, so that the variation in light resistance in the plane of the film can be suppressed. [{(Mp1+Mp2) / 2}-Tg1] is usually larger than 0°C, preferably 3°C or more, and more preferably 5°C or more. The upper limit of [{(Mp1+Mp2) / 2}-Tg1] is, for example, 65° C. or less, preferably 40° C. or less, and more preferably 20° C. or less.

[0025] The melting point Mp1 of the ultraviolet absorber [1] can be measured by using a differential scanning calorimeter (DSC). This measurement can be performed under a nitrogen atmosphere at a temperature increase rate of 10°C / min. The melting point Mp2 of the hindered amine light stabilizer [1] can be measured by the same method as the measurement method for the melting point Mp1 of the ultraviolet absorber [1].

[0026] The glass transition temperature Tg1 of the thermoplastic resin [1] can be measured by differential scanning calorimetry based on JIS K 7121. This measurement can be performed under the conditions of heating a sample from room temperature to 200°C at 20°C / min, then cooling to 40°C at 20°C / min, and then heating from 40°C to 200°C at 10°C / min.

[0027] [2.2. Components of Layer A] Layer A contains at least a thermoplastic resin [1], an ultraviolet absorber [1], and a hindered amine light stabilizer [1], and each of the above components is independently contained in a specific ratio. In the optical laminate film according to this embodiment, the "ratio of a certain component to the entirety of a certain component layer" refers to the ratio of the amount of a certain component to the total amount of solid components of a certain component layer.

[0028] [2.2.1. Thermoplastic resin [1]] The thermoplastic resin [1] contained in the layer A has a glass transition temperature Tg1 (° C.) and contains an alicyclic structure-containing polymer.

[0029] The glass transition temperature Tg1 (°C) of the thermoplastic resin [1] is not particularly limited as long as it satisfies the formula (2). From the viewpoint of improving the heat resistance of the optical laminate film, the glass transition temperature Tg1 (°C) of the thermoplastic resin [1] is preferably 120°C or higher, particularly preferably 140°C or higher, and preferably 200°C or lower, more preferably 180°C or lower, particularly preferably 170°C or lower. The glass transition temperature Tg1 (°C) of the thermoplastic resin [1] can be adjusted, for example, by the type and amount of the alicyclic structure-containing polymer.

[0030] Thermoplastic resins [1] include polymers containing alicyclic structures. The alicyclic structure-containing polymer is a polymer containing an alicyclic structure in a repeating unit. The alicyclic structure-containing polymer is usually excellent in mechanical strength, transparency, low water absorption, moisture resistance, dimensional stability and light weight. The alicyclic structure-containing polymer may be amorphous or crystalline.

[0031] Examples of the alicyclic structure-containing polymer include a polymer obtained by polymerization reaction using a cyclic olefin as a monomer, or a hydrogenated product thereof. In addition, the alicyclic structure-containing polymer may be either a polymer containing an alicyclic structure in the main chain or a polymer containing an alicyclic structure in the side chain. Among them, the alicyclic structure-containing polymer preferably contains an alicyclic structure in the main chain. Examples of the alicyclic structure include a cycloalkane structure and a cycloalkene structure, and the cycloalkane structure is preferred from the viewpoint of thermal stability and the like.

[0032] The number of carbon atoms contained in one alicyclic structure is preferably 4 or more, more preferably 5 or more, more preferably 6 or more, and is preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less. When the number of carbon atoms contained in one alicyclic structure is within the above range, mechanical strength, heat resistance, and moldability are highly balanced.

[0033] The proportion of repeating units having an alicyclic structure in the alicyclic structure-containing polymer is preferably 30% by weight or more, more preferably 50% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more. By increasing the proportion of repeating units having an alicyclic structure as described above, heat resistance can be improved. In the alicyclic structure-containing polymer, the remainder other than the repeating unit having the alicyclic structure is not particularly limited and can be appropriately selected depending on the intended use.

[0034] Examples of the polymer containing an alicyclic structure include (1) norbornene-based polymers, (2) monocyclic olefin polymers, (3) cyclic conjugated diene polymers, (4) vinyl alicyclic hydrocarbon polymers, and hydrogenated versions thereof. Among these, norbornene-based polymers and hydrogenated versions thereof are preferred from the viewpoints of transparency and moldability.

[0035] Examples of norbornene-based polymers include ring-opening polymers of monomers having a norbornene structure and their hydrogenated products; addition polymers of monomers having a norbornene structure and their hydrogenated products. Examples of ring-opening polymers of monomers having a norbornene structure include ring-opening homopolymers of one type of monomer having a norbornene structure, ring-opening copolymers of two or more types of monomers having a norbornene structure, and ring-opening copolymers of a monomer having a norbornene structure and any monomer that can be copolymerized therewith. Examples of addition polymers of monomers having a norbornene structure include addition homopolymers of one type of monomer having a norbornene structure, addition copolymers of two or more types of monomers having a norbornene structure, and addition copolymers of a monomer having a norbornene structure and any monomer that can be copolymerized therewith. Among these, the hydrogenated ring-opening polymers of monomers having a norbornene structure are particularly suitable from the viewpoints of moldability, heat resistance, low moisture absorption, low moisture permeability, dimensional stability, and light weight.

[0036] Examples of monomers having a norbornene structure include bicyclo[2.2.1]hept-2-ene (common name: norbornene), tricyclo[4.3.0.1 2,5 ]Deca-3,7-diene (common name: dicyclopentadiene), 7,8-benzotricyclo[4.3.0.1 2,5 ]deca-3-ene (common name: methanotetrahydrofluorene), tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodec-3-ene (trivial name: tetracyclododecene) and derivatives of these compounds (for example, those having a substituent on the ring). Examples of the substituent include an alkyl group, an alkylene group, and a polar group. These substituents may be the same or different, and a plurality of them may be bonded to the ring. The monomer having a norbornene structure may be used alone or in combination of two or more kinds in any ratio.

[0037] A ring-opening polymer of a monomer having a norbornene structure can be produced, for example, by polymerizing or copolymerizing the monomer in the presence of a ring-opening polymerization catalyst.

[0038] An addition polymer of a monomer having a norbornene structure can be produced, for example, by polymerizing or copolymerizing the monomer in the presence of an addition polymerization catalyst.

[0039] The hydrogenated products of the ring-opening polymer and the addition polymer described above can be produced, for example, by hydrogenating the carbon-carbon unsaturated bonds in a solution of the ring-opening polymer and the addition polymer in the presence of a hydrogenation catalyst containing a transition metal such as nickel or palladium, preferably to 90% or more.

[0040] The weight average molecular weight (Mw) of the alicyclic structure-containing polymer is preferably 10,000 or more, more preferably 15,000 or more, and even more preferably 20,000 or more, and is preferably 100,000 or less, more preferably 80,000 or less, and even more preferably 50,000 or less. The alicyclic structure-containing polymer having such a weight average molecular weight has an excellent balance of mechanical strength, moldability, and heat resistance.

[0041] The molecular weight distribution (Mw / Mn) of the alicyclic structure-containing polymer is preferably 1.2 or more, more preferably 1.5 or more, particularly preferably 1.8 or more, and is preferably 3.5 or less, more preferably 3.4 or less, particularly preferably 3.3 or less. When the molecular weight distribution is the lower limit of the above range or more, the productivity of the alicyclic structure-containing polymer can be increased and the production cost can be reduced. When the molecular weight distribution is the upper limit or less, the amount of low molecular weight components is reduced, so that the stability of the layer containing the alicyclic structure-containing polymer can be improved.

[0042] The weight average molecular weight Mw and number average molecular weight Mn of the alicyclic structure-containing polymer can be measured in terms of polyisoprene by gel permeation chromatography (hereinafter abbreviated as "GPC") using cyclohexane as a solvent. If the resin does not dissolve in cyclohexane, they can be measured in terms of polystyrene by GPC using toluene as a solvent.

[0043] The glass transition temperature of the alicyclic structure-containing polymer is preferably 50° C. or higher, more preferably 70° C. or higher, particularly preferably 80° C. or higher, and is preferably 200° C. or lower, more preferably 180° C. or lower, particularly preferably 170° C. or lower. The glass transition temperature of the alicyclic structure-containing polymer can be measured in the same manner as the glass transition temperature Tg1 (° C.) of the thermoplastic resin [1] described above.

[0044] As the thermoplastic resin containing the alicyclic structure-containing polymer, various products are commercially available, and one having the desired properties can be appropriately selected and used. Examples of such commercially available products include the product groups "ZEONOR" (manufactured by Zeon Corporation), "Arton" (manufactured by JSR Corporation), "Apel" (manufactured by Mitsui Chemicals, Inc.), and "TOPAS" (manufactured by Polyplastics Co., Ltd.).

[0045] The thermoplastic resin [1] may contain one type of alicyclic structure-containing polymer alone, or may contain two or more types in any ratio. The thermoplastic resin [1] may contain any polymer other than the alicyclic structure-containing polymer as long as it does not impair the effects of the present invention, but from the viewpoint of significantly exhibiting the effects of the present invention, it is preferable that the amount of the optional polymer is small. The ratio of the optional polymer to 100 parts by weight of the thermoplastic resin [1] is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and may be 0 parts by weight or more, preferably 0 parts by weight.

[0046] The proportion of the thermoplastic resin [1] in the entire layer A is usually 70% by weight or more, preferably 80% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more, and usually 99.8% by weight or less, preferably 98% by weight or less, and more preferably 97% by weight or less. When the amount of the resin containing the alicyclic structure-containing polymer is within the above range, the layer A can have the properties possessed by the alicyclic structure-containing polymer.

[0047] [2.2.2. Ultraviolet absorbers [1]] The ultraviolet absorber [1] contained in the layer A has a melting point Mp1 that satisfies the above formulas (1) and (2).

[0048] The melting point Mp1 (°C) of the ultraviolet absorber [1] is not particularly limited as long as it satisfies the above formulae (1) and (2), but is preferably 180°C or higher and 200°C or lower.

[0049] The ultraviolet absorbent [1] may be appropriately selected from the following ultraviolet absorbents.

[0050] As the ultraviolet absorber, an ultraviolet absorber composed of an organic compound is preferable, and among them, at least one ultraviolet absorber selected from the group consisting of a benzotriazole-based ultraviolet absorber, a triazine-based ultraviolet absorber, and a benzophenone-based ultraviolet absorber is particularly preferable.

[0051] Examples of benzotriazole-based ultraviolet absorbers include 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-butylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidylmethyl)phenol, methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 reaction product, 2-(2H-benzotriazol-2-yl)-6-(straight-chain and side-chain dodecyl)-4-methylphenol, etc. Examples of commercially available triazole-based ultraviolet absorbers include "ADEKA STAB LA-31" manufactured by ADEKA Corporation and "TINUVIN 329" manufactured by BASF Corporation.

[0052] Examples of triazine-based ultraviolet absorbers include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine, etc. Examples of commercially available triazine-based ultraviolet absorbers include "Tinuvin 1577" manufactured by BASF.

[0053] Benzophenone-based ultraviolet absorbers include, for example, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone 2',4'-di-tert-butylphenyl-3,5-di-tert-4-hydroxybenzoate, etc. Commercially available products of such benzophenone-based ultraviolet absorbers include, for example, "Seesorb 712" manufactured by Shipro Chemical Co., Ltd.

[0054] The proportion of the ultraviolet absorber [1] in the entire Layer A is preferably 0.1 wt % or more, more preferably 0.5 wt % or more, particularly preferably 5 wt % or more, and is preferably 20 wt % or less, more preferably 10 wt % or less.

[0055] [2.2.3. Hindered amine light stabilizers [1]] The hindered amine light stabilizer [1] contained in the layer A has a melting point Mp2 that satisfies the above formulas (1) and (2).

[0056] The melting point Mp2 (°C) of the hindered amine light stabilizer [1] is not particularly limited as long as it satisfies the above formulae (1) and (2), but is preferably 120°C or higher and 180°C or lower.

[0057] The hindered amine light stabilizer [1] may be appropriately selected from the following hindered amine light stabilizers.

[0058] Examples of the hindered amine light stabilizer include compounds having a 2,2,6,6-tetramethyl-4-piperidyl group which may have a substituent, such as 2,2,6,6-tetramethyl-4-piperidyl esters of carboxylic acids which may have a substituent (e.g., 2,2,6,6-tetramethyl-4-piperidyl methacrylate, 1,2,2,6,6-pentamethyl-4-piperidyl stearate, 2,2,6,6-tetramethyl-4-piperidyl benzoate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, tetrakis(2 ,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, bis(2,2,6,6-tetramethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,4,4-pentamethyl-4-piperidyl)- 2-Butyl-2-(3,5-di-tert-butyl-4-hydroxybenzyl)malonate, 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinol / diethyl succinate polycondensate, bis{4-(1-octyloxy-2,2,6,6-tetramethyl)piperidyl}decanedionate), 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-morpholino-s-triazine polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4 -dichloro-6-tert-octylamino-s-triazine polycondensate, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-s-triazin-6-yl]-1,5,8,12-tetraazadodecane, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl]-1,5,8-12-tetraazadodecane, 1,6,11-tris[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-s-triazin-6-yl]aminoundecane, 1,6,11-tris[2,4-bis(N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl]aminoundecane, bis{4-(2,2,6,6-tetramethyl-1-undecyloxy)piperidyl}carbonate, reaction products of 1,6-hexanediamine, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-polymer, 2,4,6-trichloro-1,3,5,triazine, N-butyl-1-butanamine, and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, etc. Commercially available examples of such hindered amine light stabilizers include "ADEKA STAB LA-57" manufactured by ADEKA Corporation, "KIMASSORB 2020FDL" manufactured by BASF Corporation, and "TINUVIN 770" manufactured by BASF Corporation.

[0059] The proportion of the hindered amine [1] in the entire layer A is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, and is preferably 10% by weight or less, more preferably 5% by weight or less.

[0060] [2.2.4.Optional components] In addition to the thermoplastic resin [1], ultraviolet absorber [1], and hindered amine-based light stabilizer [1], the A layer may contain any optional component as long as it does not interfere with the effects of the present invention. Examples of the optional components include stabilizers such as antioxidants, heat stabilizers, and near-infrared absorbers; resin modifiers such as lubricants and plasticizers; colorants such as dyes and pigments; and antistatic agents. The A layer may contain one type of optional component alone, or may contain two or more types in any ratio. However, from the viewpoint of significantly exerting the effects of the present invention, it is preferable that the A layer does not contain any optional component, and therefore it is preferable that the A layer contains only the thermoplastic resin [1], ultraviolet absorber [1], and hindered amine-based light stabilizer [1].

[0061] [2.3. Thickness of intermediate layer] The thickness of the intermediate layer can be set according to the intended use of the optical laminate film according to this embodiment. The specific thickness of the intermediate layer is preferably 9 μm or more, more preferably 15 μm or more, particularly preferably 20 μm or more, and is preferably 80 μm or less, more preferably 70 μm or less, particularly preferably 60 μm or less.

[0062] 3. First outer layer and second outer layer The first outer layer is a layer disposed on one surface side of the intermediate layer. The first outer layer may be in direct contact with the intermediate layer or may be disposed via another layer, but the former is preferable. The second outer layer is a layer disposed on the surface side of the intermediate layer opposite to the first outer layer side. The second outer layer may be in direct contact with the intermediate layer or may be disposed via another layer, but the former is preferable. Here, "direct contact" between two layers means that there is no other layer between the two layers.

[0063] The optical laminate film according to this embodiment has the first outer layer and the second outer layer, and thus can suppress bleeding out of additives such as an ultraviolet absorber and a hindered amine-based light stabilizer from the intermediate layer.

[0064] The first outer layer and the second outer layer may be made of the same material and have the same thickness, or may be made of the same material but different thicknesses, or may be made of materials with different component types, component weight ratios, etc. From the viewpoint of facilitating the production of the optical laminate film and suppressing curling of the optical laminate film, it is preferable that they are made of the same material and have the same thickness.

[0065] The resin layers used as the first and second outer layers usually contain a thermoplastic resin, and may contain additives as necessary. The thermoplastic resin may or may not contain an alicyclic structure-containing polymer, but from the viewpoint of increasing the adhesive strength with the intermediate layer, the former is preferable, and it is more preferable to contain the same thermoplastic resin [1] as the intermediate layer. In addition, from the viewpoint of improving the slipperiness of the optical laminate film, the first and second outer layers are preferably layers containing particles.

[0066] As described above, the first outer layer and the second outer layer are preferably made of the same material and have the same thickness, and preferably contain a thermoplastic resin [1] and particles as the constituent materials. Therefore, in this embodiment, the first outer layer and the second outer layer are preferably B layers each independently containing an alicyclic structure-containing polymer [1] and particles at a specific ratio. As shown in FIG. 1, in the optical laminate film 10, when the first outer layer 111 and the second outer layer 112 are each independently B layers, the optical laminate film 10 has a laminate structure in which the first outer layer (B), the intermediate layer (A), and the second outer layer (B) are arranged in this order in the thickness direction.

[0067] [3.1. Components of Layer B] The layer B contains at least a thermoplastic resin [1] and particles, and contains each of the above components in a specific ratio.

[0068] [3.1.1. Thermoplastic resin [1]] Layer B contains a thermoplastic resin [1]. That is, layer B contains the same thermoplastic resin as layer A. By containing the same thermoplastic resin as layer A, the affinity between layer A and layer B can be increased, and the adhesive strength can be increased.

[0069] When Layer B is used as the first outer layer and the second outer layer, the glass transition temperature Tg1 (°C) of the thermoplastic resin [1] is preferably 120°C or higher, particularly preferably 160°C or higher, and preferably 200°C or lower, more preferably 180°C or lower, particularly preferably 170°C or lower. When Tg1 is in the above-mentioned range, the heat resistance of the optical laminate film can be increased.

[0070] The proportion of the thermoplastic resin [1] in the entire B layer is preferably 90% by weight or more, and more preferably 95% by weight or more, based on 100% by weight of the total solid components of B layer, and is usually 98.8% by weight or less, and preferably 97% by weight or less.

[0071] [3.1.2. Particles] The B layer contains particles. The particles may be inorganic particles made of inorganic materials, organic particles made of organic materials, or composite particles containing a combination of inorganic and organic materials. Examples of materials for inorganic particles include inorganic oxides such as silica, titania, alumina, and zirconia; calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, and calcium phosphate. Examples of materials for organic particles include silicone resins, fluororesins, and acrylic resins. These may be used alone or in combination of two or more at any ratio.

[0072] Among these exemplified particle materials, silica is preferable because silica particles have excellent transparency, are unlikely to cause internal haze, and are not colored, and therefore have little effect on the optical properties of the optical laminate film.

[0073] As the silica particles, commercially available products may be used. Examples of commercially available products include "Eposter MX-050W" (average particle size 80 nm), "Seahoster KE-W10" (average particle size 110 nm), and "Eposter MX-100W" (average particle size 150 nm to 200 nm) manufactured by Nippon Shokubai Co., Ltd.; "Snowtex MP-2040" (average particle size 150 nm to 200 nm) manufactured by Nissan Chemical Co., Ltd.; "Adomafine SO-C1" (average particle size 0.3 μm) and "Adomana YC100C" (average particle size 0.1 μm) manufactured by Admatechs Co., Ltd.

[0074] The particles contained in layer B have an average particle size within a specific range. The specific average particle size of the particles is usually 0.01 μm or more, preferably 0.05 μm or more, and particularly preferably 0.10 μm or more, and usually 0.5 μm or less, preferably 0.4 μm or less, and particularly preferably 0.3 μm or less.

[0075] The average particle size of the particles can be measured by the following method. The particle size distribution of the particles is measured by a laser diffraction method. The particle size at which the cumulative volume calculated from the small diameter side in the measured particle size distribution is 50% can be adopted as the average particle size.

[0076] The proportion of particles in the entire layer B is usually 1% by weight or more, preferably 3% by weight or more, and usually 10% by weight or less, preferably 7% by weight or less.

[0077] [3.1.3. Ultraviolet absorbers [2]] The layer B may contain an ultraviolet absorbing agent. When the layer B contains an ultraviolet absorbing agent, the light resistance of the first outer layer and the second outer layer can be improved. In the following description, the ultraviolet absorbing agent contained in the layer B may be referred to as an ultraviolet absorbing agent [2] in order to distinguish it from the ultraviolet absorbing agent [1] contained in the layer A.

[0078] Since the B layer is used as the first outer layer and the second outer layer, it is preferable that the ultraviolet absorber [2] has high thermal stability. If the ultraviolet absorber [2] has low thermal stability, the ultraviolet absorber [2] may undergo thermal decomposition due to heat applied during the production of the film, resulting in the formation of foreign matter within the film surface. In addition, when the T-die method is used, thermal decomposition products may adhere to the die, resulting in streak-like defects in the film called die lines. For these reasons, it is preferable that the ultraviolet absorber [2] has high thermal stability.

[0079] Specifically, the 5% weight loss temperature of the ultraviolet absorber [2] is preferably 250°C or higher, more preferably 280°C or higher, and is preferably 420°C or lower, more preferably 400°C or lower.

[0080] The 5% weight loss temperature of the ultraviolet absorber [2] refers to the temperature at which the weight of the ultraviolet absorber [2] decreases by 5% compared to the weight of the measurement sample before heating when the weight change of the ultraviolet absorber [2] is measured during heating. The 5% weight loss temperature of the ultraviolet absorber [2] can be measured by observing the weight change when the sample is heated in a nitrogen atmosphere at a heating rate of 10°C / min in the range of 25°C to 600°C using a thermogravimeter.

[0081] The ultraviolet absorbent [2] may be appropriately selected from the ultraviolet absorbents described in the above section [2.2.2. Ultraviolet absorbent [1]]. In this embodiment, the ultraviolet absorbent [1] and the ultraviolet absorbent [2] may be the same ultraviolet absorbent or may be different ultraviolet absorbents.

[0082] The proportion of the ultraviolet absorber [2] in the entire B layer is preferably 0.1% by weight or more, more preferably 0.2% by weight or more, and preferably 5% by weight or less, more preferably 1% by weight or less. By setting the proportion of the ultraviolet absorber [2] within the above range, the bleed-out of the ultraviolet absorber [2] from the B layer can be suppressed. From the viewpoint of suppressing the bleed-out of the ultraviolet absorber in the optical laminate film, it is preferable that the proportion of the ultraviolet absorber [2] in the entire B layer is smaller than the proportion of the ultraviolet absorber [1] in the entire A layer.

[0083] [3.1.4. Hindered amine light stabilizers [2]] The B layer may contain a hindered amine light stabilizer. When the B layer contains a hindered amine light stabilizer, the light resistance of the first outer layer and the second outer layer can be improved. In the following description, the hindered amine light stabilizer contained in the B layer may be referred to as a hindered amine light stabilizer [2] in order to distinguish it from the hindered amine light stabilizer [1] contained in the A layer.

[0084] Since the B layer is used as the first outer layer and the second outer layer, it is preferable that the hindered amine light stabilizer [2] has high thermal stability. If the thermal stability of the hindered amine light stabilizer [2] is low, the hindered amine light stabilizer [2] may undergo thermal decomposition due to heat applied during the production of the film, resulting in the formation of foreign matter within the film surface. In addition, when the T-die method is used, the thermal decomposition product may adhere to the die, resulting in the formation of a die line on the film. For these reasons, it is preferable that the hindered amine light stabilizer [2] has high thermal stability.

[0085] Specifically, the 5% weight loss temperature of the hindered amine light stabilizer [2] is preferably 250° C. or higher, more preferably 280° C. or higher, and preferably 420° C. or lower, more preferably 400° C. or lower. The 5% weight loss temperature of the hindered amine light stabilizer [2] can be measured by the same method as the method for measuring the 5% weight loss temperature of the ultraviolet absorber [2] described above.

[0086] In the present embodiment, when Layer B contains an ultraviolet absorber [2] and a hindered amine light stabilizer [2], it is preferable that the 5% weight loss temperature of each of the ultraviolet absorber [2] and the hindered amine light stabilizer [2] is 250° C. or higher. When the 5% weight loss temperature of each of the ultraviolet absorber [2] and the hindered amine light stabilizer [2] is equal to or higher than the upper value, it is possible to effectively suppress surface defects of the optical laminate film caused by thermal decomposition of the ultraviolet absorber [2] and the hindered amine light stabilizer [2].

[0087] The hindered amine light stabilizer [2] may be appropriately selected from the hindered amine light stabilizers described above in the section [2.2.3. Hindered amine light stabilizer [1]]. In this embodiment, the hindered amine light stabilizer [1] and the hindered amine light stabilizer [2] may be the same hindered amine light stabilizer or may be different.

[0088] The proportion of the hindered amine light stabilizer [2] in the entire B layer is preferably 0.1% by weight or more, more preferably 0.2% by weight or more, and preferably 5% by weight or less, more preferably 1% by weight or less. This is because the bleed-out of the hindered amine light stabilizer [2] from the B layer can be suppressed. From the viewpoint of suppressing the bleed-out of the hindered amine light stabilizer in the optical laminate film, it is preferable that the proportion of the hindered amine light stabilizer [2] in the entire B layer is smaller than the proportion of the hindered amine light stabilizer [1] in the entire A layer.

[0089] 3.1.4. Optional Ingredients Layer B may contain optional components selected appropriately as necessary in addition to the aforementioned alicyclic structure-containing polymer [1], particles, ultraviolet absorber [2], and hindered amine-based light stabilizer [2], but it is preferable that it does not contain any optional components, and therefore it preferably contains only the alicyclic structure-containing polymer [1], particles, ultraviolet absorber [2], and hindered amine-based light stabilizer [2]. The optional components can be the same as those described in the above section [2.2.4. Optional Components], so the description here is omitted.

[0090] [3.2.Thickness of layer B] The thickness of the B layer can be set according to the purpose of use of the optical laminated film according to this embodiment. The specific thickness of the B layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, particularly preferably 1.0 μm or more, and preferably 10.0 μm or less, more preferably 8.0 μm or less, particularly preferably 6.0 μm or less. In the optical laminated film according to this embodiment, particularly when the total thickness of the optical laminated film is 10 μm or more and 100 μm or less, the thickness of the B layer is preferably 0.5 μm or more and 10 μm or less.

[0091] 4. Layer structure, thickness and physical properties of optical laminate film The optical laminated film according to this embodiment includes a first outer layer, an intermediate layer, and a second outer layer in this order. In the optical laminated film according to this embodiment, the first outer layer and the intermediate layer may be in direct contact with each other, or may be arranged through another layer. In addition, the optical laminated film may be in direct contact with the intermediate layer and the second outer layer, or may be arranged through another layer. Among them, in this embodiment, it is preferable that the first outer layer and the intermediate layer are in direct contact with each other, and the intermediate layer and the second outer layer are in direct contact with each other. This is because the adhesive strength of each layer can be increased and the optical laminated film can be made thin.

[0092] The thickness of the optical laminate film can be set to any thickness, but is preferably 10 μm or more and 100 μm or less, more preferably 10 μm or more and 80 μm or less. In this embodiment, the first outer layer, the intermediate layer and the second outer layer can all adopt a layer configuration containing an alicyclic structure-containing polymer as the layer configuration of the optical laminate film, so that the heat resistance and moisture resistance can be improved, and therefore even if the thickness of the optical laminate film is thinned to within the above range, the heat resistance and moisture resistance of the laminate film can be sufficient.

[0093] The optical laminate film may be a sheet or a long film. The optical laminate film according to the present embodiment is preferably long and in the form of a roll, since it can reduce the occurrence of defects such as blocking and scratches near the winding core. When the optical laminate film is long, the length of the laminate film may exceed 2000 m. Even when the optical laminate film according to the present embodiment is wound into a roll form by winding a long film like this, it can reduce the occurrence of defects such as blocking and scratches near the winding core as described above.

[0094] A "long" film refers to a film having a length of 5 times or more, preferably 10 times or more, the length of which is sufficient to be wound into a roll for storage or transportation. There is no particular upper limit to the length, but it is usually 100,000 times or less the width.

[0095] The width of the optical laminate film can be set according to the purpose of use of the optical laminate film. The specific width of the optical laminate film is preferably 500 mm or more, more preferably 700 mm or more, particularly preferably 1000 mm or more, and is preferably 5000 mm or less, more preferably 4000 mm or less, particularly preferably 3000 mm or less.

[0096] The haze of the optical laminate film is preferably 2.0% or less, more preferably 1.5% or less, and particularly preferably 1.0% or less. The lower limit is ideally 0.0%, but is usually 0.5% or more. The haze can be measured using a turbidimeter in accordance with JIS K7361-1997.

[0097] It is preferable that the optical laminate film has a high total light transmittance. The specific total light transmittance of the optical laminate film is preferably 85% or more, more preferably 87% or more, particularly preferably 90% or more, and ideally 100%. The total light transmittance can be measured in the wavelength range of 400 nm or more and 700 nm or less using an ultraviolet-visible spectrometer.

[0098] The optical laminate film preferably has a low ultraviolet transmittance. Specifically, the optical laminate film has a light transmittance at a wavelength of 390 nm of preferably 1% or less, more preferably 0.5% or less, even more preferably 0.2% or less, and ideally 0%. In addition, the optical laminate film preferably has a low light transmittance at a wavelength of 280 nm to 380 nm. Specifically, the optical laminate film has a light transmittance at a wavelength of 280 nm to 380 nm of preferably 1% or less, more preferably 0.5% or less, even more preferably 0.2% or less, and ideally 0%. The light transmittance at wavelengths of 390 nm and 280 nm to 380 nm can be measured using an ultraviolet-visible spectrometer.

[0099] 5. Manufacturing method of optical laminate film The optical laminated film according to one embodiment of the present invention can be manufactured by melt extrusion.As the method of manufacturing optical laminated film by melt extrusion, for example, each layer constituting optical laminated film can be manufactured as a single layer film by melt extrusion, and then, if necessary, can be bonded via an adhesive layer, or each layer constituting optical laminated film can be simultaneously formed by melt co-extrusion, but the latter is more preferred.

[0100] That is, a preferred method for producing the optical laminate film according to this embodiment includes producing the first outer layer, the intermediate layer, and the second outer layer by melt co-extrusion. As described above, in this embodiment, it is preferable that the optical laminate film has a three-layer structure in which the A layer and the B layer containing the thermoplastic resin [1] are laminated in the order of the B layer, the A layer, and the B layer, and therefore, hereinafter, a method for producing the optical laminate film having the three-layer structure will be described as an example.

[0101] Fig. 2 is a side view showing a schematic diagram of a manufacturing apparatus 200 for the optical laminate film 10 according to one embodiment of the present invention. As shown in Fig. 2, the manufacturing apparatus 200 for the optical laminate film 10 according to one embodiment of the present invention includes a molding machine 210 and a cast roll 220. Furthermore, the manufacturing apparatus 200 may include a pinning device 230 and a transport roll 240 for transporting the film, as necessary.

[0102] The molding machine 210 includes a die 212 having a lip portion 211 formed therein. The lip portion 211 is an outlet capable of discharging a molten composition as a molten resin composition, and is usually formed in a slit shape extending in one direction. The lip portion 211 is formed so that the molten composition can be extruded through the lip portion 211 to continuously form a molten film 20 as a film-like molten composition according to the shape of the lip portion 211.

[0103] The casting roll 220 is a roll member having a peripheral surface 221 capable of receiving the molten film 20, and is usually provided so that the peripheral surface 221 faces the lip portion 211 of the die 212. The casting roll 220 is configured to be rotatable in the direction indicated by the arrow A so that the molten film 20 can be transported along the film transport path on the peripheral surface 221. 220 As shown in FIG. 1, the casting roll 220 is rotatable in the circumferential direction about an axis 222. The temperature of a peripheral surface 221 of the casting roll 220 is adjusted to an appropriate temperature so that the molten film 20 received by the peripheral surface 221 can be cooled.

[0104] The pinning device 230 is a device for performing a pinning process in which a part of the molten film 20 is brought into contact with the peripheral surface 221 of the cast roll 220. Examples of the pinning device 230 include an electrostatic pinning device that applies an electric charge to the molten film, an air pinning device that blows air onto the molten film, and a touch pinning device that presses the molten film against the peripheral surface 221 with a pressing tool. With these pinning devices 230, the molten film 20 can be brought into close contact with the peripheral surface 221 of the cast roll 220 with an appropriate adhesion force, and the pinned part of the molten film 20 can be fixed to the peripheral surface 221. In addition, since air is entrained, a layer of entrained air is generally formed between the molten film 20 and the peripheral surface 221 of the cast roll 220 in the part not subjected to the pinning process.

[0105] A manufacturing method for the optical laminated film 10 using the above-mentioned manufacturing apparatus 200 typically includes a first step of obtaining resin composition A and resin composition B by a kneading method, a second step of extruding the molten composition as a molten resin composition through the lip portion 211 of the die 212 to obtain a molten film 20, and a third step of receiving the molten film 20 on the peripheral surface 221 of the casting roll 220.

[0106] In the first step, resin composition A and resin composition B are obtained by a kneading method. Resin composition A can be produced by, for example, feeding a thermoplastic resin [1], an ultraviolet absorber [1], and a hindered amine-based light stabilizer [1], and optional components as necessary, to an extruder equipped with a plurality of screws and kneading them. A twin-screw extruder can be used as the extruder. The kneading temperature is, for example, based on the glass transition temperature Tg1 (°C) of the thermoplastic resin [1], usually Tg1 or higher, preferably Tg1+5°C or higher, more preferably Tg1+10°C or higher, and preferably Tg1+250°C or lower, more preferably Tg1+200°C or lower, and more preferably Tg1+150°C or lower. In addition, the kneading temperature is, for example, based on the higher temperature Mp3 between the melting point Mp1 of the ultraviolet absorber [1] and the melting point Mp2 of the hindered amine light stabilizer [1], preferably Mp3-120°C or higher, more preferably Mp3-100°C or higher, even more preferably Mp3-50°C or higher, and preferably Mp3+250°C or lower, preferably Mp3+200°C or lower, and particularly preferably Mp3+150°C or lower. By setting the kneading temperature within the above-mentioned range, the components contained in the resin composition A can be mixed well.

[0107] Resin composition B can be produced by feeding thermoplastic resin [1] and particles, and optionally ultraviolet absorber [2], hindered amine light stabilizer [2], and optional components to the extruder and kneading them. The preferred range of the kneading temperature based on Tg1 is the same as the range of the kneading temperature of resin composition A described above. On the other hand, the range of the kneading temperature based on the higher temperature Mp4 of the ultraviolet absorber [2] and the hindered amine light stabilizer [2] is the same as the range of the kneading temperature based on Mp3 of the kneading temperature of resin composition A described above.

[0108] The kneading temperature can be adjusted, for example, by the temperature of the extruder.

[0109] In the second step, the resin composition contained in the optical laminate film 10 is co-extruded. That is, in the second step, a molten composition containing the resin composition contained in the optical laminate film 10 is extruded into a film shape through a lip portion 211 of a die 212 of a molding machine 210 to form a molten film 20. The molten composition is extruded to form a molten film 20 containing a layer of resin composition B, a layer of resin composition A, and a layer of resin composition B in this order, by extruding a molten composition containing a resin composition B for layer B, a resin composition A for layer A, and a resin composition B for layer B.

[0110] In the second step, the resin composition B, the resin composition A, and the resin composition B flow in a molten state inside the die 212, and usually form a layer like the optical laminate film 10 before passing through the lip portion 211, and are extruded through the lip portion 211 while maintaining the layer. Therefore, in order to maintain the resin composition in a molten state inside the die 212, the temperature T D is usually set higher than the glass transition temperature of the resin. D is preferably Tg1+100° C. or more, more preferably Tg1+110° C. or more, particularly preferably Tg1+120° C. or more, and is preferably Tg1+200° C. or less, more preferably Tg1+180° C. or less, particularly preferably Tg1+160° C. or less. D usually represents the temperature of the lip portion 211 of the die 212. When the temperature of the lip portion 211 is not constant in the width direction of the film (length direction of the lip portion 211), it is desirable that the average temperature of the lip portion 211 in the width direction falls within the above range.

[0111] The temperature of the resin composition extruded from the lip portion 211 is preferably uniform in the width direction of the film. Therefore, the temperature of the molten film 20 may be non-uniform in the width direction, but it is preferable that the degree of variation is small. Specifically, the temperature T of the molten film 20 measured in the width direction is R The minimum value of T Rmin and the maximum value T Rmax Difference with T Rmax -T Rminis preferably 20°C or less, more preferably 18°C ​​or less, and particularly preferably 15°C or less.

[0112] The temperature difference T Rmax -T Rmin For example, the die temperature T D This can be made small by optimizing the PID control and suppressing heat radiation from the die 212.

[0113] The dimensions of the lip part, such as lip width (dimension corresponding to the thickness of the molten film) and lip length (dimension corresponding to the width of the molten film), are preferably set according to the dimensions of the optical laminate film to be manufactured. The arithmetic mean roughness Ra of the lip part is preferably 0 μm to 1.0 μm, more preferably 0 μm to 0.7 μm, and particularly preferably 0 μm to 0.5 μm. Here, the arithmetic mean roughness Ra can be measured at a cutoff of 0.8 mm in accordance with JIS B 0601-2001. The die 212 is usually connected to an extruder (not shown) so that pressure for extruding the resin can be applied as described above.

[0114] In the third step, the molten film 20 formed as described above is received by the peripheral surface 221 of the cast roll 220. In the example shown here, the pinning process is performed by the pinning device 230 on both ends of the molten film 20 in the width direction, so that both ends of the molten film 20 are brought into contact with the peripheral surface 221 of the cast roll 220. Then, the molten film 20 is pulled by the rotating cast roll 220 and transported along the peripheral surface 221 of the cast roll 220. Then, when transported along the peripheral surface 221 in this manner, the molten film 20 is cooled. In detail, the heat of the molten film 20 may be partially dissipated into the surrounding air, but most of it is transmitted to the cast roll 220, thereby progressing the cooling of the molten film 20. The molten film 20 is hardened by this cooling, and a long optical laminate film 10 is continuously obtained.

[0115] The temperature of the peripheral surface 221 may be any within the range in which the desired optical laminate film 10 is obtained, and is preferably Tg1-50°C or higher, more preferably Tg1-40°C or higher, and particularly preferably Tg1-30°C or higher, and is also preferably Tg1°C or lower, preferably Tg1-5°C or lower, and more preferably Tg1-10°C or lower.

[0116] The optical laminate film 10 thus obtained is guided by a transport roll 240 as necessary, separated from the cast roll 220, and sent downstream. The sent optical laminate film 10 is usually collected by a collecting device (not shown).

[0117] The above-mentioned manufacturing method of the optical laminate film 10 may further include any step. For example, the above-mentioned manufacturing method may include a cooling step of further cooling the optical laminate film 10 obtained by cooling the molten film 20 with the casting roll 220 with a cooling roll (not shown). In addition, the above-mentioned manufacturing method may include, for example, a trimming step of removing the portion of the optical laminate film 10 that has come into contact with the casting roll 220 by the pinning process (in the above example, the end portion in the width direction).

[0118] In the above-mentioned manufacturing method, an example of a manufacturing method for a three-layer laminate film in which a B layer, an A layer, and a B layer are laminated in this order as an optical laminate film has been described. However, the present invention is not limited to this. For example, when a layer containing a thermoplastic resin other than the thermoplastic resin [1] is used as at least one of the first outer layer and the second outer layer, the kneading temperature, the die temperature, and the peripheral surface temperature can be adjusted by further considering the glass transition temperature of the thermoplastic resin constituting the layer and the type of optional components. EXAMPLES

[0119] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and can be modified and carried out as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto. In the following description, the units "%" and "parts" are by weight unless otherwise specified. Furthermore, the operations described below were carried out at room temperature and pressure unless otherwise specified.

[0120] [Evaluation method] (Method of measuring weight average molecular weight Mw and number average molecular weight Mn of polymer) The weight average molecular weight Mw and number average molecular weight Mn of the polymer were measured as polystyrene equivalent values ​​using a gel permeation chromatography (GPC) system (Tosoh Corporation, "HLC-8320"). In the measurement, an H-type column (Tosoh Corporation) was used as the column, and tetrahydrofuran was used as the solvent. The temperature during the measurement was 40°C.

[0121] (Method for measuring hydrogenation rate of polymer) The hydrogenation rate of the polymer is 4 as a solvent at 145°C, 1 Measured by H-NMR measurement.

[0122] (glass transition temperature Tg) The glass transition temperature Tg of the polymer was measured as follows. First, the polymer was melted by heating, and the melted polymer was quenched with dry ice. Next, the glass transition temperature Tg of the polymer was measured using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min (heating mode) using the polymer as a test specimen.

[0123] (Thickness measurement) The thickness of the film was measured using a contact thickness gauge (Mitsutoyo Co., Ltd., Code No. 543-390). The thickness of each layer in a film consisting of multiple layers was calculated from the thickness ratio obtained by observing the cross section of the film under a microscope and the thickness ratio and the total thickness of the film.

[0124] (Variation in light resistance) An optical laminate film (width 500 mm and roll length 1000 mm) was cut into 25 test pieces of 50 mm x 50 mm at 100 mm intervals in the width direction and 100 mm intervals in the length direction. Each test piece was measured using a super xenon weather meter (Suga Testing Machine SX75) at 100 w / m 2 The light resistance test was carried out for 500 hours. * Measure the b among the 25 test pieces. * If the difference between the maximum and minimum values ​​is 0.5 or less, it is classified as A, and if the difference between the maximum and minimum values ​​is 0.5 or less, it is classified as b. * If the difference between the maximum and minimum values ​​is greater than 0.5 and less than 1.0, it is B, * The difference between the maximum and minimum values ​​was rated C when it was greater than 1.0.

[0125] (Heat resistance) Three test pieces of 50mm x 50mm cut from both ends and the center of the optical laminate film were placed in a 110°C oven for one hour and heated. The dimensional change rate of the test pieces before and after heating was measured using a universal projector (Nikon Solutions V-12B). The average absolute value of the dimensional change rate was rated A if it was 0.1% or less, B if it was more than 0.1% and less than 0.5%, and C if it was more than 0.5%. The dimensional change rate is the ratio of the difference in the length of one side of the test piece after heating to the length of one side of the test piece before heating.

[0126] (Film appearance) The optical laminated film was cut into a length of 1000 mm, and the film appearance was observed visually and by a microscope. The number of die lines nd was evaluated by regarding a die line (streak-like defect) with a width of 500 μm or more as "1 line", and the number of deformed parts nt was evaluated by regarding a deformed part of the film with a longer diameter of 500 μm or more as "1 piece". As shown in Table 1, the case where the number of die lines is 3 or less and the number of deformed parts is 1 or less was evaluated as A, the case where the number of die lines is more than 3 and 10 or less and the number of deformed parts is more than 1 and 5 or less was evaluated as B, and the case where the number of die lines is more than 10 and the number of deformed parts is more than 5 was evaluated as C.

[0127] [Table 1]

[0128] [Production Example 1: Production of Thermoplastic Resin 1 Containing an Alicyclic Structure-Containing Polymer] Tricyclo[4.3.0.12,5]deca-3,7-diene (dicyclopentadiene; hereinafter, occasionally abbreviated as "DCP"), 7,8-benzotricyclo[4.4.0.12,5.17,10]deca-3-ene (methanotetrahydrofluorene; hereinafter, occasionally abbreviated as "MTF"), and tetracyclo[4.4.0.12,5.17,10]dodeca-3-ene (tetracyclododecene; hereinafter, occasionally abbreviated as "TCD") were mixed in a weight ratio of 5 / 70 / 25. This mixture was subjected to ring-opening polymerization and then hydrogenated by a known method to obtain thermoplastic resin 1 as a DCP / MTF / TCD ring-opening polymer hydrogenated product. The copolymerization ratio of each norbornene-based monomer in the obtained thermoplastic resin 1 was calculated by gas chromatography analysis from the composition of the norbornene-based monomer remaining in the solution after polymerization, and was DCP / MTF / TCD = 5 / 70 / 25, which was almost equal to the charged composition. The thermoplastic resin 1 had a weight average molecular weight (Mw) of 34,000, a molecular weight distribution (Mw / Mn; Mn is number average molecular weight) of 2.1, a hydrogenation rate of 99.9%, and a glass transition temperature Tg of 160°C.

[0129] [Production Example 2: Production of Thermoplastic Resin 2 Containing Alicyclic Structure-Containing Polymer] DCP and MTF were mixed in a weight ratio of 87 / 13. This mixture was subjected to ring-opening polymerization and then hydrogenated by a known method to obtain thermoplastic resin 2 as a DCP / MTF ring-opening polymer hydrogenate. The copolymerization ratio of each norbornene-based monomer in the obtained thermoplastic resin 2 was calculated by gas chromatography analysis from the composition of the norbornene-based monomer remaining in the solution after polymerization, and was DCP / MTF = 87 / 13, which was almost equal to the charged composition. The thermoplastic resin 2 had a weight average molecular weight (Mw) of 38,000, a molecular weight distribution (Mw / Mn; Mn is number average molecular weight) of 2.2, a hydrogenation rate of 99.9%, and a glass transition temperature Tg of 125°C.

[0130] [Production Example 3: Production of Thermoplastic Resin 3 Containing Alicyclic Structure-Containing Polymer] DCP and MTF were mixed in a weight ratio of 83 / 17. This mixture was subjected to ring-opening polymerization and then hydrogenated by a known method to obtain thermoplastic resin 3 as a DCP / MTF ring-opening polymer hydrogenate. The copolymerization ratio of each norbornene monomer in the obtained thermoplastic resin 3 was calculated by gas chromatography analysis from the composition of the norbornene monomer remaining in the solution after polymerization, and was DCP / MTF=83 / 17, which was almost equal to the charged composition. In addition, the weight average molecular weight (Mw) of this thermoplastic resin 3 was 32,000, the molecular weight distribution (Mw / Mn; Mn is the number average molecular weight) was 2.2, the hydrogenation rate was 99.9%, and the glass transition temperature Tg was 105°C.

[0131] [Example 1] (Thermoplastic resin composition A for layer A) A thermoplastic resin composition for layer A was obtained by mixing 94.5 parts of thermoplastic resin 1 obtained in Production Example 1, 5 parts of ultraviolet absorber a (ADEKA Corporation's "ADK STAB LA-31", melting point 196°C), and 0.5 parts of hindered amine light stabilizer a (ADEKA Corporation's "ADK STAB LA-57", melting point 130°C) in a twin-screw extruder.

[0132] (Thermoplastic composition B for layer B) A thermoplastic resin composition for layer B was obtained by mixing 96.4 parts of thermoplastic resin 1 obtained in Production Example 1, 3 parts of particles ("Admafine SO-C1" manufactured by Admatechs Co., Ltd.), 0.3 parts of ultraviolet absorber a, and 0.3 parts of hindered amine light stabilizer a in a ratio of 0.3 parts using a twin-screw extruder.

[0133] A film manufacturing apparatus was prepared, which included a co-extrusion film molding machine equipped with a single-layer die formed with a lip portion capable of ejecting a molten composition, a casting roll having a peripheral surface capable of receiving a molten film formed from the molten composition extruded from the lip portion of the die, a cooling roll provided downstream of the casting roll, and a winding machine provided downstream of the cooling roll. The monolayer die of the coextrusion film molding machine was equipped with a heater capable of adjusting the temperature of the monolayer die to a desired temperature. The coextrusion film molding machine also had a feed block connected to the monolayer die, and was set up so that two types of resins supplied to the feed block could be coextruded into three layers through the lip of the monolayer die. The lip length (the dimension corresponding to the width of the molten film) was 750 mm. The casting roll was provided so that its peripheral surface faced the lip of the single layer die, and was rotatable in the peripheral direction at a desired set speed. An electrostatic pinning device was provided near the peripheral surface of the casting roll, which was capable of bringing the end of the molten film into close contact with the peripheral surface at a point immediately downstream of the position where the peripheral surface received the molten film.

[0134] (Film manufacturing) The above-mentioned thermoplastic resin composition A and thermoplastic composition B were supplied to the feed block of the co-extrusion film molding machine so that a molten film having a first outer layer (B layer), an intermediate layer (A layer), and a second outer layer (B layer) in this order was obtained. The supplied thermoplastic resin composition A and thermoplastic composition B were melted and sent to a single-layer die set at 280 ° C. Then, the melted thermoplastic resin composition A and thermoplastic composition B merged in the single-layer die to form a layer, and the molten composition containing the layered thermoplastic resin composition A and thermoplastic composition B was extruded into a film shape through the lip part. The molten composition extruded from the lip part obtained a molten film having a layer of thermoplastic composition B as the first outer layer, a layer of thermoplastic resin composition A as the intermediate layer, and a layer of thermoplastic composition B as the second outer layer in this order. The molten film discharged from the lip was received on the circumferential surface of a cast roll having a circumferential surface temperature of 155°C and a circumferential speed of 5m / min. Immediately after that, the surfaces of the first outer layer side at both ends in the width direction of the molten film were brought into contact with the circumferential surface of the cast roll by an electrostatic pinning device. Then, this molten film was cooled while being conveyed downstream according to the rotation of the cast roll, and a laminated film having, in this order, a B layer corresponding to the first outer layer, an A layer corresponding to the intermediate layer, and a B layer corresponding to the second outer layer was obtained. The width of the obtained film was 500mm and the winding length was 1000m. The thicknesses of the constituent layers of the film (first outer layer / intermediate layer / second outer layer) were 2μm / 36μm / 2μm.

[0135] [Examples 2 to 6 and Comparative Examples 1 to 4] A laminated film was produced in the same manner as in Example 1, except that the thermoplastic resin compositions A and B were produced according to the compositions shown in Tables 2-4.

[0136] The abbreviations in Tables 2 to 4 have the following meanings. Table 2 shows details of the ultraviolet absorbers a to d, the hindered amine light stabilizers a to c, and the particles in Tables 4 and 5. Table 3 shows the kneading temperatures, die temperatures, and peripheral surface temperatures in Examples 1 to 6 and Comparative Examples 1 to 4. UVA: Ultraviolet absorber HALS: Hindered amine light stabilizers Tg1: Glass transition temperature of polymers containing alicyclic structures Mp1: Melting point of UV absorber Mp2: Melting point of hindered amine light stabilizer

[0137] [Table 2]

[0138] [Table 3]

[0139] [Table 4]

[0140] [Table 5]

[0141] [result] As shown in Tables 4 and 5, in Examples 1 to 6 in which the Tg1 of the thermoplastic resin, the melting point Mp1 of the ultraviolet absorber, and the hindered amine light stabilizer Mp2 satisfied the formulas (1) and (2), the variation in the light resistance of the laminate film was reduced. However, in Comparative Example 1 which did not satisfy the formulas (1) and (2), Comparative Example 3 which did not satisfy the formula (1), and Comparative Examples 2 and 4 which did not satisfy the formula (2), it was confirmed that the variation in the light resistance of the laminate film occurred. [Explanation of symbols]

[0142] 10 Optical laminated film 20 Melting Film 111 First outer layer 120 Middle Class 112 Second outer layer 200 Manufacturing equipment 210 Molding machine 211 Lip 212 Dice 220 Cast Roll 221 Peripheral surface 222 Axis 230 Pinning Device 240 Transport roll

Claims

1. An optical laminate film comprising a first outer layer, an intermediate layer, and a second outer layer in this order, the intermediate layer is an A layer containing a thermoplastic resin [1] having a glass transition temperature Tg1 (°C) and containing an alicyclic structure-containing polymer, an ultraviolet absorber [1] having a melting point Mp1 (°C), and a hindered amine-based light stabilizer [1] having a melting point Mp2 (°C), the proportion of the thermoplastic resin [1] in the entire layer A is 70% by weight or more and 99.8% by weight or less, the proportion of the ultraviolet absorber [1] is 0.1% by weight or more and 20% by weight or less, and the proportion of the hindered amine light stabilizer [1] is 0.1% by weight or more and 10% by weight or less, The glass transition temperature Tg1 (°C) of the thermoplastic resin [1] is 140°C or higher, The optical laminate film, wherein the Tg1, the Mp1 and the Mp2 satisfy the following formulas (1) and (2). |(Mp1-Mp2)|≦100(℃) (1) {(Mp1+Mp2) / 2}-Tg1>0(℃) (2)

2. The first outer layer and the second outer layer are each independently a layer B containing the thermoplastic resin [1] and particles, the ratio of the thermoplastic resin [1] in the entire layer B is 90% by weight or more and 98.8% by weight or less, and the ratio of the particles is 1% by weight or more and 10% by weight or less, The optical laminate film according to claim 1, wherein the glass transition temperature Tg1 (°C) of the thermoplastic resin [1] is 120°C or higher.

3. An optical laminate film comprising a first outer layer, an intermediate layer, and a second outer layer in this order, the intermediate layer is an A layer containing a thermoplastic resin [1] having a glass transition temperature Tg1 (°C) and containing an alicyclic structure-containing polymer, an ultraviolet absorber [1] having a melting point Mp1 (°C), and a hindered amine-based light stabilizer [1] having a melting point Mp2 (°C), the proportion of the thermoplastic resin [1] in the entire layer A is 70% by weight or more and 99.8% by weight or less, the proportion of the ultraviolet absorber [1] is 0.1% by weight or more and 20% by weight or less, and the proportion of the hindered amine light stabilizer [1] is 0.1% by weight or more and 10% by weight or less, The Tg1, the Mp1, and the Mp2 satisfy the following formulas (1) and (2), The first outer layer and the second outer layer are each independently a layer B containing the thermoplastic resin [1] and particles, the ratio of the thermoplastic resin [1] in the entire layer B is 90% by weight or more and 98.8% by weight or less, and the ratio of the particles is 1% by weight or more and 10% by weight or less, The glass transition temperature Tg1 (°C) of the thermoplastic resin [1] is 120°C or higher. Optical laminate film. |(Mp1-Mp2)|≦100(℃) (1) {(Mp1+Mp2) / 2}-Tg1>0(℃) (2)

4. the layer B contains an ultraviolet absorber [2] and a hindered amine light stabilizer [2], the proportion of the ultraviolet absorber [2] in the entire layer B is 0.1% by weight or more and 5% by weight or less, and the proportion of the hindered amine light stabilizer [2] is 0.1% by weight or more and 5% by weight or less, The optical laminate film according to claim 2 or 3, wherein the ultraviolet absorber [2] and the hindered amine light stabilizer [2] each independently have a 5% thermal weight loss temperature of 250°C or higher.

5. The optical laminate film according to any one of claims 2 to 4, wherein the total thickness of the optical laminate film is 10 μm or more and 100 μm or less, and the thickness of the B layer is 0.5 μm or more and 10 μm or less.

6. The optical laminate film according to any one of claims 1 to 5, wherein the haze (HZ) of the optical laminate film is 2% or less.

7. A method for producing the optical laminate film according to any one of claims 1 to 6, A method for producing an optical laminate film, comprising producing the first outer layer, the intermediate layer, and the second outer layer by melt coextrusion.

Citation Information

Patent Citations

  • Multilayered structural cycloolefinic resin film, polarization plate and liquid crystal display device

    JP2007261052A

  • Agricultural multilayer film

    JP2017023038A

  • Optical film, optical film manufacturing method, and polarizer

    JP2017116759A

  • Method for producing thermoplastic resin composition

    JP2020033517A

  • Laminate and circularly polarizing plate

    JP2021086038A